Experimental investigation on green ceramic machining with nanosecond laser source. (January 2021) - Demarbaix, Anthonin; Ducobu, François; Juste, Enrique; Petit, Fabrice; Duterte, Charles; Rivière-Lorphèvre, Edouard
Highlights: Study of laser machining with nanosecond source on the ceramic at green stage. The factorial design is applied to determine the influence of input laser parameters. Development of image processing software to characterize the sintering area. The pulse overlap influences considerably the sintering unlike the power. The input slicing parameter should be determined when other parameters are fixed. Abstract: Yttrium oxide tetragonal zirconia polycrystals (Y-TZP) is an inert bioceramic used for many bio-implantable applications that request a high accuracy which is difficult to achieve with the current technologies. Laser machining of hard ceramic is difficult because the interaction of the laser beam with the material can lead to microcracks and surface modifications of the microstructure. In order to tackle those problems, machining can be carried out on the green ceramic to avoid the microcracks apparition and machining time is reduced thanks to an improvement of the powder preparation. Unfortunately, the thermal exchange can lead to a local sintering which reduces the mechanical properties of the final part. This paper shows the influence of 4 input laser parameters during the laser machining on green ceramic using an experimental plan. The study shows the impact of these parameters on roughness, local sintering, and machined depth. Roughness and local sintering depend on the spot overlap which links the repetition rate and the feed rate. The average power has little influence on the sintering in contrast to the spot overlap. The slicing must be chosen after setting the other machining parameters because it depends directly on the blank composition. The optimal parameters are an average power of 15 W, a feed rate of 1100 mm/s, a repetition rate of 15 kHz and a slicing of 5 μm.